The old man and the sea - Taylor, Jud, 1940-; Hirson, Roger O.; Quinn, Anthony, 1915-2001; Cruz, Alexis; Cole, Gary, 1957-; Hemingway, Ernest, 1899-1961; Fuisz Robert E.; Yordshire Television; Koch Vision (Port Washington, NY : Koch Vision (manufacturer) [and] (distributer), 2005)
The story of the old Cuban fisherman and his epic battle with sharks for his giant fish
Based on the novel by Ernest Hemingway
Director of photography, Tony Imi ; art director, Les Tomkins ; production designer, Malcolm J. Middleton ; editor, Fredric Steinkamp ; music, Bruce Broughton
Cast : Anthony Quinn, Alexis Cruz, Gary Cole, Patricia Clarkson, Joe Santos, Valentina Quinn, Francesco Quinn, Paul Calderon, Sully Diaz
DVD, Dolby digital stereo
Keywords: Heminway, Ernest, -- 1899-1961 -- Film and video adaptations; Fishing -- Drama